2008
DOI: 10.1177/1066896908319675
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Osteoblastoma: A Case Report Involving a Unique Chromosomal Aberration

Abstract: Osteoblastomas are rare bone-producing neoplasms that generally occur in the young and can be misdiagnosed as an osteosarcoma if correlation with clinical history, radiology, and histology is not carefully considered or if the several variants of osteoblastoma are not recognized. These variants lie on a morphologic spectrum between conventional osteoblastoma and osteosarcoma. Aggressive osteoblastoma is one such subtype. As the name implies, the histologic features of aggressive osteoblastoma may appear malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 16 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…Although the balanced translocation found was unique, the authors could not unequivocally state whether the abnormality provided any insight into differentiating CO, AO, or OB-like OS. They concluded that cytogenetic studies are not yet useful for either diagnostic or prognostic purposes with these challenging lesions and concurred with others that careful correlation of clinical, radiographic and histologic findings is paramount to proper patient management [19].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although the balanced translocation found was unique, the authors could not unequivocally state whether the abnormality provided any insight into differentiating CO, AO, or OB-like OS. They concluded that cytogenetic studies are not yet useful for either diagnostic or prognostic purposes with these challenging lesions and concurred with others that careful correlation of clinical, radiographic and histologic findings is paramount to proper patient management [19].…”
Section: Discussionmentioning
confidence: 67%
“…Baker et al reported a case of a unique chromosomal aberration in aggressive osteoblastoma of the femoral diaphysis of a 12-year-old girl. The cytogenetic analysis performed in that case showed that of the 22 metaphases analyzed, 20 revealed a pseudodiploid clone with a balanced translocation between chromosomes 4, 7, and 14 [19]. Although the balanced translocation found was unique, the authors could not unequivocally state whether the abnormality provided any insight into differentiating CO, AO, or OB-like OS.…”
Section: Discussionmentioning
confidence: 89%
“…Histologically, osteoblastomas are similar to osteoid osteomas, both producing osteoid and primitive woven bone amidst fibrovascular connective tissue. Although the tumor is usually considered benign, a controversial aggressive variant has been described in the literature, with histologic features similar to those of malignant tumors such as osteosarcomas [1,5,20]. Differential diagnosis of scaphoïd bone tumors should also include intraosseous ganglion cysts, aneurismal bone cyst, enchondroma, giant cell tumor and osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Rossner and al [21,22] reported mutation of the p53 gene at exon 5 in a patient with malignant osteoblastoma. Radig and al [21,22] described another mutation at exon 7 in a patient with osteoblastoma-like osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation